EFFECTS OF MARITAL SATISFACTION AND RITUAL UTILITY ON BEREAVEMENT EXPERIENCE IN ABORTION - Oliveira, Catarina Meneses de; Silva, Ana Dóris; Ramalho, Carla; Costa, Maria Emília; Martins, Mariana Veloso (Cogitare Enfermagem, 2022)
Objective: The present study analyzed the effects of the use and perceived usefulness of bereavement rituals and marital satisfaction on perinatal bereavement. Method: 74 Portuguese women who attended a public hospital in Porto - Portugal, after experiencing one or more abortions in 2019, responded to a self-report survey. The effects of ritual utility and marital satisfaction on bereavement experience, as well as interaction effects, were analyzed. Results: With adjustment to bereavement after pregnancy loss as the dependent variable, a negative effect of marital satisfaction (b=.33) and a positive effect of ritual utility (b =.46) were observed. No significant moderation effect was observed. Conclusion: This study highlights the importance of addressing bereavement rituals and conjugality in providing emotional support for the loss, with the figure of the nurse being paramount in the contexts of abortion and neonatal loss.